(untitled) (Revista Española de Derecho Internacional, 2008)
The increasing ressource by Western Countries, Spain included, to the practice of diplomatic assurances as a mean to make possible forced transfer of persons to States in which there is a risk of torture constitutes one more of the challenges that fight against terrorim causes to human rights. Perhaps influenced by disclosures that reveals unacceptable abuses in this ambit, recent rulings from international human rights supervisory bodies, reaffirming the absolute character of non-refoulement against torture and rejecting diplomatic assurances in several cases, seem to announce a tougher attitude in respect of this practice.